Analiza rozwoju rynku telefonii mobilnej w Polsce w latach 2002-2013 - Kaczmarczyk, Paweł (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The purpose of this article is to analyze the changes and current state of the Polish mobile telephony market. The thesis of the article states that a multiple increase in demand for telecommunication services has been observed on the Polish mobile telephony market in 2002–2013. The article describes the transformation of the Polish mobile telephony market based on its demonopolization and liberalisation. The quantitative research was based on the annual statistical data of Central Statistical Office and reports of Office of Electronic Communications.